Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.7717/peerj-cs.105
|View full text |Cite
|
Sign up to set email alerts
|

Challenges as enablers for high quality Linked Data: insights from the Semantic Publishing Challenge

Abstract: While most challenges organized so far in the Semantic Web domain are focused on comparing tools with respect to different criteria such as their features and competencies, or exploiting semantically enriched data, the Semantic Web Evaluation Challenges series, co-located with the ESWC Semantic Web Conference, aims to compare them based on their output, namely the produced dataset. The Semantic Publishing Challenge is one of these challenges. Its goal is to involve participants in extracting data from heteroge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Inconsistencies are introduced when the rules are defined. Indicatively, the Semantic Publishing Challenge required different solutions to generate knowledge graphs from the CEUR-WS proceedings [14]. It was observed that, despite the fact that these solutions were provided by Semantic Web experts, the data was modeled differently and each solution introduced different inconsistencies.…”
Section: Knowledge Graph Generationmentioning
confidence: 99%
“…Inconsistencies are introduced when the rules are defined. Indicatively, the Semantic Publishing Challenge required different solutions to generate knowledge graphs from the CEUR-WS proceedings [14]. It was observed that, despite the fact that these solutions were provided by Semantic Web experts, the data was modeled differently and each solution introduced different inconsistencies.…”
Section: Knowledge Graph Generationmentioning
confidence: 99%